Analisis kerjasama sekolah dengan dunia usaha dan dunia industri dalam meningkatkan mutu lulusan sekolah menengah kejuruan - Feronika Munthe; Yulius Mataputun (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study aims to analyze the school's collaboration with industry and business community (DU/DI) in improving the quality of Vocational High School (SMK) graduates. This study applies a qualitative descriptive approach of case study design at SMK Negeri 3 Jayapura. The researcher as the key instrument of the research conducted an in-depth interview with principals, teachers/public relations, students, school committees, supervisors as well as industry and business community (DU/DI). Participatory observation and document analysis were also utilized in order to support the data gathering process. The techniques for validating the data were gathered by extending the time of observation, peer discussion and triangulation. The data was analyzed qualitatively by means of data reduction, data display, and drawing conclusions/verification. The results of this study indicate that the school's collaboration with industry and business community (DU/DI) in improving the quality of SMK Negeri 3 Jayapura is favorable but still needs some improvement. It still requires some adjustments in term of alignment of the data-based industry-based curriculum which involves industry and business community (DU/DI) from its early establishment, the presence of industrial teachers which has not yet touched the substance of industrial practice and the absorption of graduates is still limited to MoUs bound by contracts and high-achieving graduates.